Incidencia de embarazos no planificados como consecuencia de la inefectividad de métodos anticonceptivos hormonales en el Hospital Alfredo Noboa Montenegro periodo noviembre 2023- abril 2024. - Larenas Llanos, Anshy Tamara (2024)
The present curriculum research work aimed to establish the incidence of unintended pregnancies as a result of the ineffectiveness of hormonal contraceptive methods at the Alfredo Noboa Montenegro Hospital, Bolívar Province, Ecuador, during the period from November 2023 to April 2024. A field research with a quantitative approach, descriptive level, and cross-sectional design was conducted. The study population consisted of 657 pregnant women attended in the hospital's Gynecology-Obstetrics service, with a sample of 100 women who met the inclusion criteria. The results indicated that 47% of the patients were between 15 and 25 years old, and 53% belonged to the indigenous ethnic group. The most commonly used contraceptive method was the injectable (63%), followed by the oral method (30%). However, adherence to these methods was low, with 72% of the patients reporting inconsistent use. It was found that low adherence and incorrect use of contraceptive methods were significantly associated with pregnancy complications, such as preeclampsia and fetal death. The study concludes that low adherence to hormonal contraceptive methods is a determining factor in the high incidence of unintended pregnancies and associated complications. The effectiveness of these methods largely depends on their correct and continuous use, highlighting the need to reinforce educational interventions and clinical follow-up to improve the health outcomes of patients.